Answer:
The correct answer is B⊂A.
Step-by-step explanation:
The sets are:
A={x|x is a polygon}
B={x|x is a triangle}
According to the given sets Option 2 is correct:
The correct option is B⊂A.. We will read it as B is a subset of A.
The reason is that the Set A contains polygon and Set B contains triangle. A triangle is also a simplest form of polygon having 3 sides and 3 angles but a polygon has many other types also. Like hexagon, pentagon, quadrilateral etc. All the triangles are included in the set of polygon.
Thus the correct answer is B⊂A....
Write the expression in complete factored form. 2n^2(q+8)-(q+8)=
(q+8)(2n^2-1)
I think this is the correct form.
what is the mean between 500, 372,536, 369, 328, 412 & 561
Answer:
439.7.
Step-by-step explanation:
The mean of these number is
(500+372+536+ 328 +369+412+561) / 7
=439.7.
Final answer:
To determine the mean of the numbers 500, 372, 536, 369, 328, 412, and 561, you add them together and divide by the total count, which results in a mean of approximately 439.71.
Explanation:
To find the mean of a set of numbers, you add up all the numbers and then divide by the number of values in the set. The numbers given are 500, 372, 536, 369, 328, 412, and 561. Let's calculate the mean step by step:
Add up all the numbers: 500 + 372 + 536 + 369 + 328 + 412 + 561 = 3078.Count the number of values: There are 7 numbers in total.Divide the total sum by the number of values: 3078 ÷ 7 = 439.7142857.The mean (average) of the numbers is approximately 439.71.
Find the num
The sum of a number and its reciprocal 10/3. find the number 5
Answer:
x=3 or x= 1/3
Step-by-step explanation:
Let the number = x
The reciprocal of the number = 1/x
According to the given statement:
x+1/x=10/3
x²+1/x=10/3
3(x²+1)=10x
3x²+3=10x
Move 10x to the L.H.S
3x²-10x+3=0
Break the middle term:
3x²-9x-x+3=0
3x(x-3)-1(x-3)=0
(x-3)(3x-1)=0
x-3=0 , 3x-1=0
x=0+3 , 3x=0+1
x=3 , 3x=1
x=3 ,x = 1/3
So x=3 or x= 1/3 ....
A basket contains six apples and four peaches. You randomly select one piece of fruit and eat it. Then you randomly select another piece of fruit. The first piece of fruit is an apple and the second piece is a peach. Find the probability of this occuring.
Answer as a fraction: 4/15
Answer as a decimal: 0.267
The decimal version is approximate rounded to three decimal places.
=============================================================
Explanation:
6 apples, 4 peaches
6+4 = 10 pieces of fruit total
The probability of picking an apple is 6/10 = 3/5
After you pick and eat the apple, there are 10-1 = 9 pieces of fruit left. Also, the probability of picking a peach is 4/9, as there are 4 peaches out of 9 fruit left over.
Multiply out 3/5 and 4/9 to get (3/5)*(4/9) = (3*4)/(5*9) = 12/45 = 4/15
Using a calculator, 4/15 = 0.267 approximately.
Answer:
Fraction: [tex]\frac{4}{15}[/tex]
Decimal: [tex]0.2667[/tex]
Percent: 26.67%
Step-by-step explanation:
If the basket contains six apples and four peaches then the Total amount of fruit in the basket is (6+4) 10 pieces of fruit.
You reach in and randomly pick out an apple. Since there are only 4 apples, the probability of this happening was [tex]\frac{4}{10}[/tex] , and now there are only 9 pieces of fruit in the basket.
Now you reach in and randomly pick out a peach. Since there are 6 peaches, the probability of this happening is [tex]\frac{6}{9}[/tex]. Now we can find the probability of both of these things happening one after another by multiplying both probabilities together
[tex]\frac{4}{10} * \frac{6}{9} = \frac{24}{90}[/tex]
[tex]\frac{24}{90} = \frac{4}{15}[/tex] ...... simplified
So we can see that the probability of you picking out an apple and a peach in sequence is [tex]\frac{4}{15}[/tex] or [tex]0.2667[/tex]
I hope this answered your question. If you have any more questions feel free to ask away at Brainly.
What is the solution to the equation below?
log 20х3 - 2logx = 4
x=25
x=50
x=250
x=500
Answer:
x = 500.
Step-by-step explanation:
log20x^3 - 2logx = 4
By the laws of logs:
log20x^3 - logx^2 = 4
log(20x^3 / x^2) = 4
20x^3 / x^2 = 10^4
20x = 10,000
x = 10,000 / 20
x = 500.
The solution of the given logarithmic equation is x = 500.
What is a logarithmic equation?Any equation in the variable x that contains a logarithm is called a logarithmic equation.
Given logarithmic equation
[tex]log20x^{3} -2logx=4[/tex]
Using [tex]mloga=loga^{m}[/tex]
[tex]log20x^{3} -logx^{2}=4[/tex]
Using [tex]loga-logb=log(\frac{a}{b})[/tex]
[tex]\frac{log20x^{3} }{x^{2} }=4[/tex]
[tex]log20x=4[/tex]
[tex]20x=10^{4}[/tex]
[tex]x=\frac{10000}{20}[/tex]
[tex]x=500[/tex]
The solution of the given logarithmic equation is x = 500.
Find out more information about logarithmic equation here
https://brainly.com/question/14411365
#SPJ2
Express each ratio as a fraction in lowest terms.
1) 77 to 490
2) 35 to 135
3) 65:1001
If f(x) = x^2 + 1 and g(x) = x - 4, which value is equivalent to (fºg)(10)?
Answer:
37
Step-by-step explanation:
Substitute x = 10 into g(x), then substitute the result into f(x)
g(10) = 10 - 4 = 6, then
f(6) = 6² + 1 = 36 + 1 = 37
The fuel consumption in miles per gallon for a car varies inversely with its weight. Suppose a car that weighs 2800 pounds get 33 miles per gallon on the highway. Write the equation that relates y, the fuel consumption in miles per gallon, to the car's weight, w pounds.
Answer:
y=0.01179/w
Step-by-step explanation:
First understand that the fuel consumption in miles per gallon is inversely proportional to the weight of a car.
If y is the fuel consumption in miles per gallon and w is weight of car in pounds . you can write the first statement as;
y∝1/w
Introduce a constant value for proportionality, k
y=k/w....................make k subject of the formula by multiplying both sides by 1/w
k=y/w
Given in the question that ;
w=2800
y=33
k=?
To find k , apply the formula that you derived above
k=y/w
k=33/2800 =0.011785⇒0.01178(4 significant figures)
Rewrite the formula as
y=k/w ⇒ y=0.01179/w
The equation that relates y and w is;
y=0.01179/w
The fuel consumption in miles per gallon for a car varies inversely with its weight and can be represented mathematically by the inverse proportionality relationship y = k/w. Substituting the given values gives us the constant k = 92400, so the final equation is y = 92400/w.
Explanation:This problem can be defined mathematically by an inverse proportionality relationship, expressed as y = k/w, where k is a constant, y is the fuel consumption in miles per gallon, and w is the weight of the car in pounds.
To find the value of k, we can substitute the given values into the equation. This gives us 33 = k/2800, which simplifies to k = 33 * 2800, or k = 92400.
So, the equation that relates the mileage per gallon, y, to the weight of the car, w, is y = 92400/w. This means the fuel efficiency of a car decreases as its weight increases, thus heavier cars tend to have lower miles per gallon.
Learn more about Inverse Proportionality here:https://brainly.com/question/14437120
#SPJ3
Add the two expressions.
−2.4n−3 and −7.8n+2
Enter your answer in the box.
Answer:
-10.2n - 1
Step-by-step explanation:
−2.4n − 3 + (−7.8n + 2) =
= -2.4n - 7.8n - 3 + 2
= -10.2n - 1
Answer:
-10.2n -1
Step-by-step explanation:
−2.4n−3 + −7.8n+2
Combine like terms
−2.4n −7.8n -3+2
-10.2n -1
Consider the polynomial p(x)=x^3-9x^2+18x-25, which can be rewritten as p(x)=(x-7)(x^2-2x+4)+3. The number blank is the remainder when p(x) is divided by x-7, and so x-7 blank a factor of p(x). Fill in the two blanks with is, 3, 7,is not, or 0!!!!
PLEASE HELP. WILL MARK BRAINLIEST!!
Answer:
[tex]\boxed{\text{3; is not}}[/tex]
Step-by-step explanation:
[tex]\begin{array}{rcl}p(x) & = & (x - 7)(x^{2} - 2x + 4) + 3\\\\\dfrac{p(x)}{x - 7} & = &x^{2} - 2x + 4 + \dfrac{3 }{x-7 }\\\\\end{array}\\\\\text{The number }\boxed{\mathbf{3}}\text{ is the remainder when $p(x)$ is divided by $(x - 7)$,}\\\\\text{so $(x - 7)$ }\boxed{\textbf{is not}} \text{ a factor of $p(x)$.}[/tex]
When Θ = 5 pi over 6, what are the reference angle and the sign values for sine, cosine, and tangent? Θ' = negative pi over 6; sine and cosine are positive, tangent is negative. Θ' = 5 pi over 6; sine and tangent are positive, cosine is negative Θ' = pi over 6; sine is positive, cosine and tangent are negative Θ' = negative 5 pi over 6; sine is positive, cosine and tangent are negative
Answer:
Option C is correct.
Step-by-step explanation:
[tex]\theta=\frac{5\pi }{6}[/tex]
We need to find reference angle and signs of sinФ, cosФ and tanФ
We know that [tex]\theta=\frac{5\pi }{6}radians[/tex] is equal to 150°
and 150° is in 2nd quadrant.
So, Ф is in 2nd quadrant.
And In 2nd quadrant sine is positive, while cos and tan are negative
The reference angle Ф' is found by: π - Ф
=> Ф = 5π/6
so, Reference angle Ф' = π - 5π/6
Ф' = 6π - 5π/6
Ф' = π/6
So, Option C Θ' = pi over 6; sine is positive, cosine and tangent are negative is correct.
6 plus 9 rquals to 10 plus WHAT NUMBER????
Answer: 5.
Step-by-step explanation:
6+9 = 15
10 + x = 15
-10 -10
x = 5
Answer:
x=5
Step-by-step explanation:
6+9=10+x
15=10+x
x=15-10
x=5
The area of the triangle is given by the functions area of triangle A:x2 + x area of triangle B: x2 - 3x which functions represents the sum of the areas of the two triangles? 1. 4x 2.-4x 3.x2-4x 4.2x2-2x
Answer:
4. 2x^2 - 2x.
Step-by-step explanation:
Adding the 2 functions:
Area of the 2 triangles = x^2 + x + x^2 - 3x
= .2x^2 - 2x
Answer:
OPTION 4
Step-by-step explanation:
Let be f(x) the function that represents the area of Triangle A:
[tex]f(x)=x^2 + x[/tex]
Let be g(x) the function that represents the area of Triangle B:
[tex]g(x)=x^2 - 3x[/tex]
Then, you need to add the area of Triangle A and the area of Triangle B in order to find the sum of the areas (Let be h(x) the function that represents the sum of the the areas of triangles A and B):
Therefore, this is:
[tex]h(x)=(x^2 + x)+(x^2 - 3x)=x^2 + x+x^2 - 3x=2x^2-2x[/tex]
You can notice that this matches with the option 4.
The table shows the number of degrees the temperature increased or decreased over four days. On which day did the temperature change have the greatest magnitude?
simplify. rewrite the expression in the form 9^n:
9^-3/9^12
Answer:
9 ^ (-15)
Step-by-step explanation:
9^-3/9^12
We know that a^b/ a^c = a^(b-c)
9^-3/9^12 = 9 ^(-3-12)
=9^(-15)
The expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
From the question,
we are to rewrite the given expression (9^-3/9^12) in the form 9^n
First, write the expressions properly.
The given expression is
[tex]\frac{9^{-3}}{9^{12} }[/tex]
To rewrite the given expression in the form [tex]9^{n}[/tex], we will use the division law of indices
From the division law of indices, we have that
[tex]x^{y} \div x^{z}= x^{y-z}[/tex]
Then, the given expression becomes
[tex]\frac{9^{-3}}{9^{12} } = 9^{-3} \div 9^{12}[/tex]
[tex]= 9^{-3-12}[/tex]
[tex]=9^{-15}[/tex]
Hence, the expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
Learn more here: https://brainly.com/question/18205419
A 26 foot rope is used to brace a tent pole at the county fair. the rope is anchored 10 feet from the box of the pole. How tall is the pole? (answers above^^)
Using the Pythagorean theorem a^2 + b^2 = c^2 where a and b are the side and bottom of the triangle and c is the hypotenuse ( length of rope).
Let the tent pole = a
Lhe distance from the pole be b = 10 ft.
The length of rope would vce c = 26 ft.
Now you have:
a^2 + 10^2 = 26^2
Simplify:
a^2 + 100 = 676
Now subtract 100 from each side:
a^2 = 576
To get a, take the square root of both sides:
a = √576
a = 24
The tent pole is B. 24 ft
For Sophia's graduation party, several tables of the same width will be arranged end to end to form a serving table with a
total area of 75 ft. The total length of the tables will be two more than three times the width. Find the length and width of
the serving table so that Sophia can purchase the correct table cloth. Round your answers to the nearest tenth.
Area: 75 ft
Bw + 2
Answer:
Width=4.7 ft
Length=16.1 ft
Step-by-step explanation:
Let the width of the table to be x ft
Then the length should be two more than three times the width= 2+3x ft
The area of the serving table should be 75 ft²
But you know the area of this table is calculated by multiplying the length by the width of the table
Hence, Area= length× width
Length=x ft and width =2+3x ft
75ft²= (x ft) × (2+3x ft)
[tex]75=x*(2+3x)\\\\75=2x+3x^2\\\\3x^2+2x-75=0[/tex]
Apply the quadratic formula to solve this quadratic equation
The formula is ;
x= (-b ±√b²-4ac)÷2ac
where a=3, b=2 and c=-75
x= (-2 ± √2²-4×3×-75)÷(2×3)
x=(-2±√4+900)÷6
x=(-2±√904)÷6
x=(-2±30.1)÷6
x=(-2+30.1)÷6=4.683⇒4.7(nearest tenth)
or
x=(-2-30.1)÷6= -32.1÷6=-5.35⇒ -5.4
Taking the positive value
x=width =4.7 ft
2+3x= length= 2+3(4.7)=16.1 ft
Question number 8 please please fast
Answer:
[tex]a_n=-\frac{1}{n}[/tex]
[tex]a_6=-\frac{1}{6}[/tex] is our sixth term.
[tex]a_7=-\frac{1}{7}[/tex] is our seventh term.
[tex]a_8=-\frac{1}{8}[/tex] is our eighth term.
Step-by-step explanation:
So every number in this sequence is -.
If you write 1 as 1/1, then you should see the numerator is constant one while the denominator is going up by 1 each time.
So the patter is
[tex]a_n=-\frac{1}{n}[/tex]
Test if you like:
n=1 gives us [tex]a_1=-\frac{1}{1}=-1[/tex] which is our first term.
n=2 gives us [tex]a_2=-\frac{1}{2}[/tex] which is our second term.
n=3 gives us [tex]a_3=-\frac{1}{3}[/tex] which is our third term.
n=4 gives us [tex]a_4=-\frac{1}{4}[/tex] which is our fourth term.
n=5 gives us [tex]a_5=-\frac{1}{5}[/tex] which is our fifth term.
Now we are going to use [tex]a_n=-\frac{1}{n}[/tex]
to write our next three terms:
n=6 gives us [tex]a_6=-\frac{1}{6}[/tex] which is our sixth term.
n=7 gives us [tex]a_7=-\frac{1}{7}[/tex] which is our seventh term.
n=8 gives us [tex]a_8=-\frac{1}{8}[/tex] which is our eighth term.
how much must you deposit in an account that pays 6.25% interest compounded annually to have a balance of $700 after 2 years
Answer:
[tex]\$620.07[/tex]
Step-by-step explanation:
we know that
The compound interest formula is equal to
[tex]A=P(1+\frac{r}{n})^{nt}[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
[tex]t=2\ years\\A=\$700\\ r=0.0625\\n=1[/tex]
substitute in the formula above and solve for P
[tex]700=P*(1+\frac{0.0625}{1})^{2}[/tex]
[tex]700=P*(1.0625)^{2}[/tex]
[tex]P=700/(1.0625)^{2}[/tex]
[tex]P=\$620.07[/tex]
A triangle has two sides of lengths 10 and 14. What value could the third side be?
Answer:B, C, D, E.
Step-by-step explanation:
The third side of a triangle with two sides measuring 10 and 14 units must be greater than 4 and less than 24 units. This is determined using the Triangle Inequality Theorem.
The possible values for the third side of a triangle with sides of lengths 10 and 14 can be found using the Triangle Inequality Theorem.
Add the two given side lengths: 10 + 14 = 24.
To find the range of possible values for the third side, subtract the two given side lengths from the total: 24 - 10 = 14, and 24 - 14 = 10.
Therefore, the third side of the triangle must have a length greater than 4 but less than 24.
Which of the following is a polynomial?
O A. x2-1
O B. -2
O c. 1 +2
OD.
Which are correct representations of the inequality –3(2x – 5) < 5(2 – x)? Check all that apply.
x < 5
–6x – 5 < 10 – x
–6x + 15 < 10 – 5x
Answer:
[tex]-6x+15< 10-5x[/tex]
Step-by-step explanation:
we have
[tex]-3(2x-5) < 5(2-x)[/tex]
solve for x
eliminate the parenthesis (apply the distributive property)
[tex]-3*2x+3*5 < 5*2-5*x[/tex]
[tex]-6x+15< 10-5x[/tex] ---> correct representation of the inequality
Adds (5x-15) both sides
[tex]-6x+15+5x-15< 10-5x+5x-15[/tex]
[tex]-x< -5[/tex]
Multiply by -1 both sides
[tex]x>5[/tex]
A: What are the solutions to the quadratic equation?
B: which statements accurately interpret the solution?
Answer:
A. x = -1 or x = 3B. firstStep-by-step explanation:
[tex]x^2-2x-3=0\\\\x^2+x-3x-3=0\\\\x(x+1)-3(x+1)=0\\\\(x+1)(x-3)=0\iff x+1=0\ \vee\ x-3=0\\\\x+1=0\qquad\text{subtract 1 from both sides}\\x=-1\\\\x-3=0\qquad\text{add 3 to both sides}\\x=3[/tex]
Find the mean of the data set that consists of 3, 11, 4, 3, 10, 6, 4, 5.
A. 3 and 4
B. 4.5
C. 5.75
D. 5.25
Answer:
5.75
Step-by-step explanation:
[tex]3 + 11 + 4 + 3 + 10 + 6 + 4 + 5 = 46 \\ 46 \div 8 = 5.75[/tex]
The total amount of numbers are : 8
To find the mean, we calculate the sum of all values and divide that sum by the amount of numbers there are.
PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL :)
[tex]4c - d - c - 3d[/tex]
[tex]\tt 4c-d-c-3d=3c-4d[/tex]
Answer:
3c -4d
Step-by-step explanation:
4c -d -c -3d
Combine like terms
4c -c -d -3d
3c -4d
Help please the graphs below Have the same shape. What is the equation of the blue graph
Answer:
D. G(x) = (x+2)^2
Step-by-step explanation:
We can easily solve this problem by graphing each case with a graphing calculator or any plotting tool.
The equations are
A. G(x) = (x-2)^2
B. G(x) = (x)^2 + 2
C. G(x) = (x)^2 -2
D. G(x) = (x+2)^2
Se attached image.
The correct option is
D. G(x) = (x+2)^2
Answer:
C. G(x)=x²-2
Step-by-step explanation:
The midpoint of the graph has been displaced from x=0 to x=-2. this is a negative displacement.
Therefore the new equation G(x)=x²-2
This is because there is no tilt in the graph so it is a replica of the red graph.
Which is the graph of linear inequality 2 y > x – 2?
Answer:
Third graph
Step-by-step explanation:
We are determine whether which of the given graphs is that of the linear inequality [tex]2y>x-2[/tex].
We know that, on the graph the greater than sign ([tex]>[/tex]) represents the shaded part above the line and less than sign ([tex]<[/tex]) represents the shaded region below the line.
While the signs [tex]\leq[/tex] or [tex]\geq[/tex] is denoted by a solid line on the graph.
Therefore, the third graph represents the given inequality.
Answer:
The graph in the attached figure
Step-by-step explanation:
we have
2y > x-2
The solution of this inequality is the shaded area above the dotted line 2y=x-2
The graph in the attached figure
Which is the best estimate of the circumference of this circle?
Answer:
12 is the best estimate
Answer:
option A.
Step-by-step explanation:
We have to find the circumference of the given circle with radius 2 units.
Since formula to calculate circumference of a circle is = 2πr
Where r = radius of the circle.
Circumference = 2 × (3.14) × (2)
= 4 × 3.14
= 12.56
So approximate value will be option A.
Solve x - (-9) = -14. -23 23 -5 5
Answer:
-23 = x
Step-by-step explanation:
-(-9) = 9
The thing with double negatives is that they form a plus sign, so that is really a POSITIVE nine. Therefore you do the inverse to find x: -14 - 9 = -23.
I am joyous to assist you anytime.
Answer:
[tex]\Huge \boxed{X=-23}[/tex]
Step-by-step explanation:
[tex]\displaystyle x+9=-14[/tex]
[tex]\Large\textnormal{First, subtract by 9 from both sides of equation.}[/tex]
[tex]\displaystyle x+9-9=-14-9[/tex]
[tex]\Large\textnormal{Simplify, to find the answer.}[/tex]
[tex]\displaystyle -14-9=-23[/tex]
[tex]\Large\textnormal{x=-23, which is our answer.}[/tex]
Students observing a caterpillar crawl on a tree noticed that the caterpillar crawled upwards 38 of an inch every minute. The caterpillar was already 4.5 feet off the ground when the students began observing.
Which function represents the total number of inches the caterpillar crawls after x minutes?
f(x) = 4.5x + 3/8
f(x) = 54x + 3/8
f(x( = 3/8x + 54
f(x) = 3/8x + 4.5
Answer:
f(x) = 4.5x + 3/8
Answer: Third Option
[tex]f(x) = \frac{3}{8}x + 54[/tex]
Step-by-step explanation:
We want to propose an equation that models the distance traveled by the caterpillar as a function of time, we have a constant initial quantity of 4.5 feet and then we know that every minute the caterpillar advances 3/8 of an inch
Then the distance that the caterpillar to advanced after x minutes is:
[tex]f(x) = \frac{3}{8}x[/tex]
Then we know that initially the caterpillar was at a distance of 4.5 feet or 54 inch
Then the equation for the distance in inch is:
[tex]f(x) = \frac{3}{8}x + 54[/tex]